Co-occurrence of Antibiotic and Heavy Metal Resistance and Sequence Type Diversity of Vibrio parahaemolyticus Isolated From Penaeus vannamei at Freshwater Farms, Seawater Farms, and Markets in Zhejiang Province, China - Jiang, Han; Yu, Ting; Yang, Yuting; Yu, Shengtao; Wu, Jiangchun; Lin, Rumeng; Li, Yixian; Fang, Jiehong; Zhu, Cheng (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus is the leading cause of seafood-borne bacterial poisoning in China and is a threat to human health worldwide. The aim of this study was to assess the antibiotic resistance profiles and distribution of heavy metal resistance of V. parahaemolyticus strains isolated of Penaeus vannamei from freshwater farms, seawater farms and their corresponding markets in Zhejiang, China and to assess the relationship between multi drug resistance (MDR) and multi heavy metal resistance (MHMR). Of the 360 P. vannamei samples that we tested, 90 (25.00%) were V. parahaemolyticus-positive, but the occurrence of pathogenic strains carrying the toxic genes tdh (1.11%) and trh (0.84%) was extremely low. None of the tested isolates harbored both the tdh and trh genes. However, antibiotic resistance profiles varied among different sampling locations, levels of resistance to the antibiotics ampicillin (76.67%) and streptomycin (74.44%) were high overall, and MDR isolates were common (40.00% of all isolates). Heavy metal resistance patterns were similar among the different sampling locations. Overall, the majority of V. parahaemolyticus isolates displayed tolerance to Cd2+ (60.00%), and fewer were resistant to Cu2+ (40.00%), Zn2+ (38.89%), Ni2+ (24.44%), Cr3+ (14.44%) and Co2+ (8.89%). In addition, 34.44% (31/90) of strains tested in this study were found to be MHMR. Using Pearson’s correlation analysis, MDR and MHMR were found to be positively correlated (P = 0.004; R = 0.759). The 18 V. parahaemolyticus isolates that were both MDR and MHMR represented 18 sequence types, of which 12 were novel to the PubMLST database, and displayed a high level of genetic diversity, suggesting that dissemination may be affected by mobile genetic elements via horizontal gene transfer. However, a low percentage of class 1 integrons without carrying gene cassettes and no class 2 or 3 integrons were detected in the 18 isolates as well as in all 90 V. parahaemolyticus isolates. Thus, we suggest future research to focus on elucidating mechanisms that lead to the high prevalence of resistance determinants in V. parahaemolyticus. The results of this study provide data that will support aquatic animal health management and food safety risk assessments in the aquaculture industry.